SINERGI EMPAT PILAR KEBANGSAAN DALAM MEWUJUDKAN SISWA/I BERDAYA SAING GLOBAL: PENGABDIAN MASYARAKAT DI SMAN 2 KOTA SORONG - Novalin M. Syauta; Weron Murary; Chesye Liklikwatil (Ensiklopedia of Journal, 2025)
Abstract: This community service activity aims to instill an understanding of national values through the synergy of the four pillars (Pancasila, UUD 1945, NKRI, and Bhinne ka Tunggal Ika) as the basis for students' character in the global era. The activity was carried out for 3 hours on June 12, 2025 at SMAN 2 Kota Sorong, involving 25 students in grades XI and XII. The methods used were material delivery, questions and answers, and interactive games. The results of the activity show that the Community Service synergy of the Four Pillars of Nationality can be applied effectively in the educational environment to form students with strong, adaptive characters, and are able to compete globally. National values are not an obstacle, but rather an important foundation in facing the global era. Students' understanding of the Four Pillars of Nationality at SMAN 2 Sorong City is quite good conceptually, especially in the aspect of basic introduction such as the contents and functions of Pancasila, the 1945 Constitution, the Republic of Indonesia, and Bhinneka Tunggal Ika. However, this understanding still needs to be improved in terms of implementation and relevance to everyday life and global challenges. In addition, the implementation of the Four Pillars of Nationality has been integrated into various school activities, both through subjects and in extracurricular activities. Keywords: Four Pillars of Nationality, Student Character, Globalization, Community Service, SMAN 2 Sorong.